1963
DOI: 10.3181/00379727-114-28582
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation Between Gastrin and Histamine in Stimulation of Gastric Secretion.

Abstract: During studies on Heidenhain pouches in dogs we noted that the responses to certain combinations of gastrin extract plus histamine were greater than would be anticipated on the basis of summation of stimulatory effects ( 1 ) .The study reported here was performed to determine whether the combination of gastrin plus histamine resulted in true potentiation of stimulation of secretion of acid.Methods. Four dogs with Heidenhain pouches were fasted overnight before each study and studies were performed no oftener t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
2

Year Published

1968
1968
1978
1978

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 2 publications
1
20
0
2
Order By: Relevance
“…Maximal responses to histamine and gastrin are equal in dogs with vagally innervated main stomach (gastric fistulas) when the drugs are given by continuous intravenous infusion (Passaro & Grossman, 1964). However, the maximal acid response of the vagally denervated Heidenhain pouch to gastrin is only 45 % of that to histamine (Gillespie & Grossman, 1963).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Maximal responses to histamine and gastrin are equal in dogs with vagally innervated main stomach (gastric fistulas) when the drugs are given by continuous intravenous infusion (Passaro & Grossman, 1964). However, the maximal acid response of the vagally denervated Heidenhain pouch to gastrin is only 45 % of that to histamine (Gillespie & Grossman, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…No inhibitory effects of histamine on the isolated dog gastric mucosa were observed at histamine concentrations up to 8 x 10-4 M. In vivo, supramaximal doses of histamine infusion have been demonstrated to produce a comparable or a slightly lower secretary rate than maximal acid secretion in the gastric fistula preparation (Marks, Komarov & Shay, 1960) and in the Heidenhain pouch (Gillespie & Grossman, 1963). Intravenous infusions of gastrin (Gillespie & Grossman, 1963) and acetylcholine into the arteries of the gastric fundus of the dog (Pevsner & Grossman, 1955) have been demonstrated to elicit stimulation of acid secretion at low dosage rates and suppression of acid secretion at high rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grossman et al reported that the maximal response to combination of two agents was greater than the maximal responses to either agent alone in dogs with Heidenhain pouch for the com bination of bethanechol plus gastrin (19) and gastrin plus histamine (20). Although, as Makhlouf et al (11) pointed out, the few attempts to demonstrate such potentiation in human subjects have not succeeded.…”
Section: Discussionmentioning
confidence: 89%